PEGylated Carboxyhemoglobin Bovine (SANGUINATE): Results of a Phase I Clinical Trial. Issue 8 (12th August 2014) - Misra, Hemant; Lickliter, Jason; Kazo, Friedericke; Abuchowski, Abraham
Abstract PEGylated carboxyhemoglobin bovine (SANGUINATE) is a dual action carbon monoxide releasing (CO)/oxygen (O2) transfer agent for the treatment of hypoxia. Its components inhibit vasoconstriction, decrease extravasation, limit reactive oxygen species production, enhance blood rheology, and deliver oxygen to the tissues. Animal models of cerebral ischemia, peripheral ischemia, and myocardial ischemia demonstrated SANGUINATE's efficacy in reducing myocardial infarct size, limiting necrosis from cerebral ischemia, and promoting more rapid recovery from hind limb ischemia. In a Phase I trial, three cohorts of eight healthy volunteers received single ascending doses of 80, 120, or 160 mg/kg of SANGUINATE. Two volunteers within each cohort served as a saline control. There were no serious adverse events. Serum haptoglobin decreased, but did not appear to be dose related. The T1/2 was dose dependent and ranged from 7.9 to 13.8 h. In addition to the Phase I trial, SANGUINATE was used under an expanded access emergency Investigational New Drug. SANGUINATE was found to be safe and well tolerated in a Phase I clinical trial, and therefore it will advance into further clinical trials in patients.